The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 18 PRACTICAL RULES FOR THE CONSERVATION OF VITAMINS IN THE PREPARATION AND COOKING OF GREEN VEGETABLES. 1. Obtain as fresh as possible. 2. Keep in a cool damp place in order to reduce wilting. 3. Take precautions to avoid damage due to crushing or bruising during transport or handling. 4. If vegetables are soaked use salt water (2 teasp. to 1 pint). 3. If vegetables are to be shredded or finely chopped for salads, prepare immediately before serving. 6. Use the smallest possible amount of water for cooking. 7. Have water boiling before adding vegetables. 8. Add salt to water before adding vegetables. 9. Add vegetables gradually or in small amounts at a time, in order to prevent water going off the boil. 10. Cook vegetables no longer than is necessary to render them tender. 11. Plan cooking arrangements so that vegetables are dished up and served immediately after they are cooked. On no account allow to stand for a long time on a hot plate. 12. If there is water left after cooking, drain off and use in the preparation of soups and gravies ; alternatively, if successive batches are being cooked on the same day, use the same water again adding more if necessary. METHODS RECOMMENDED WHICH RESULT IN THE LEAST LOSS OF VITAMIN C. Method I. Boil for the shortest time in a small quantity of boiling salted water. Use water left over for boiling other batches and for addition to soups and gravies. Method II. Slice the fresh vegetables into ribbons about 2 to 3 inches long by 3/4 inch wide and cook briskly for 1/2 to 1 minute in a small quantity of hot oil or dripping to which salt has been added (2 teasp. oil and 1/2 teasp. salt to an average sized cabbage). Add a small quantity of boiling water (1/2 to 1 cupful for above) and stew for about 10 minutes in a closed container. Keep the lid on so that no steam escapes. When the vegetables are cooked only a very little water should be left. This method is used throughout the Far East and India. In Europe the nearest approach to it is the French method of "casserole" or "conservative" cooking by which the vegetables are placed in a closed fireproof dish with a little water and fat and cooked in the oven or over a low flame for 13 to 25 minutes. In hay-box cookery vitamin C is destroyed so that this method should not generally be used for cooking green vegetables which are particularly valuable in the diet for their vitamin C content. Steaming of vegetables even with the best equipment is not as satisfactory as the methods described above. Conservation of Salts. If the precautions described above are carefully taken, it can be relied on that effective conservation of the valuable salts present in green vegetables will also be secured. 1(16255) Wt. 2365—866 12,506 4/42 D.L. G. 372 127/NU/5/5/1/28